Antiretroviral Treatment in Sub-Saharan Africa : Challenges and Prospects - Rahel Mesfin; Getnet Tizazu Fetene (Book collections on Project MUSE., 2013)
The introduction of antiretroviral therapy (ART) in middle and low income countries is arguably one of the most meaningful outcomes recorded in the fight against HIV and AIDS. A record number of some 6.2 million people living with HIV and AIDS are reported to be benefiting from the treatment, which is reported to have risen by 19 per cent between 2010 and 2011 and as a result of this, the region has also enjoyed a significant decline in AIDS mortality. This volume is the outcome of the ëcall for abstractsí put out by OSSREA in 2011 for senior researchers, social scientists and practitioners to.